Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Ce sexe qui n'en est pas un - Irigaray, Luce (Collection Critique, 1977)
Comment parler de l’autre côté, se demanda Alice. Car, en fait de merveilles, elle avait découvert qu’elle était plus d’une, et qu’une seule langue ne pouvait signifier ce qui avait lieu entre elles. Il fallait pourtant essayer de se faire entendre. Alors, s’appliquant, elle reprit : Que dire d’une sexualité féminine autre ? Autre que celle prescrite dans et par l’économie du pouvoir phallique. Autre que celle encore et toujours décrite – et normalisée – par la psychanalyse. Comment inventer, ou retrouver, son langage ? Comment interpréter le fonctionnement social à partir de l’exploitation des corps sexués des femmes ? Que peut être, dès lors, leur action par rapport au politique? Doivent-elles ou non intervenir dans les institutions ? Par quel biais échapper à la culture patriarcale ? Quelles questions poser à son discours ? À ses théories ? À ses sciences ? Comment les énoncer pour qu’elles ne soient pas, à nouveau, soumises à la censure ou au refoulement ? Mais aussi : comment déjà parler femme ? En retraversant le discours dominant. En interrogeant la maîtrise des hommes. En parlant aux femmes, entre femmes. Questions – parmi d’autres – qui s’interrogent et se répondent dans plusieurs langues, sur plusieurs tons, à plusieurs voix. Déconcertant l’uniformité d’un discours, la monotonie d’un genre, l’autocratie d’un sexe. Innombrables les désirs des femmes, et jamais réductibles à l’un ni à son multiple. Le jour était déjà levé depuis longtemps. Une histoire n’en finissait pas d’imposer son ordre. De l’obliger à s’exposer dans une clarté un peu froide. Dans l’attente d’un autre matin, elle repassa derrière le miroir, et elle se retrouva entre elles toute(s). Luce Irigaray
Keywords: 1900-1999; 1970-1979; corps; cours; cycles supérieurs; différence des sexes; discipline; europe; fem1000; fem7000; france; har4600; langage féminin; lit3220; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité féminine; thématiques; écriture des femmes*